PENDEKATAN BARU DALAM PEMBELAJARAN AKUNTANSI : IMPLEMENTASI COA QUARTET DI SMAN 6 CIMAHI - Riani Tanjung; Mohamad Nurkamal Fauzan (Universitas Merdeka Madiun, 2024)
Accounting learning in high schools is often perceived as boring and difficult by many students. At SMAN 6 Cimahi, the learning model employed involves teacher lectures, instructions to complete student worksheets (LKS), and individual interactive computer games. While this method has its advantages, there is a need for a more innovative and collaborative approach. This PKM examines the implementation of the CoA Quartet method, a game-based learning approach that promotes teamwork and healthy competition, in an effort to enhance student engagement, understanding, and social skills. The CoA Quartet consists of various activities that encourage student collaboration to solve accounting tasks in an interactive and enjoyable way. An evaluation was conducted through questionnaires filled out by 180 students after the CoA Quartet was implemented. Data analysis using the Chi-square test showed that this method had a significant impact on student engagement, increasing their interest and understanding in accounting learning. The results of this study support the application of CoA Quartet as an effective method in high school accounting education. The PKM also provides recommendations for implementing similar methods in other schools to improve the quality of accounting education.